2012
DOI: 10.1002/ange.201202134
|View full text |Cite
|
Sign up to set email alerts
|

Lichtgesteuerte Werkzeuge

Abstract: Die zeitliche und räumliche Kontrolle über chemische und biologische Prozesse spielt eine Schlüsselrolle im Leben, wo das Ganze oft viel mehr ist als die Summe seiner Einzelteile. Trivialerweise bilden die Moleküle einer Zelle noch lange kein lebendiges System aus, wenn sie lediglich willkürlich angeordnet werden. Wenn wir diese Zusammenhänge und die Probleme, die durch Fehlfunktionen entstehen, verstehen wollen, benötigen wir Werkzeuge, mit denen wir komplexe Experimente für diese Fragestellungen entwickeln k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
79
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(95 citation statements)
references
References 440 publications
(956 reference statements)
0
79
0
16
Order By: Relevance
“…[16,17] Photocages based on oNB remain the dominant technology to study signal transduction mediated by biomolecules despite limitations like slow analyte-release kinetics, the requirement of UV light for photolysis and the formation of potentially toxic nitroso photoproducts. [18] In addition to these shortcomings, incorporating ligands into an oNBscaffold can interfere with the uncaging mechanism. Both classes of photocaged complexes described above often exhibit low quantum yields (< 5 %) owing to resonance between receptor donor atoms and the reactive aci-nitro intermediate generated by irradiating oNB chromophores.…”
mentioning
confidence: 99%
“…[16,17] Photocages based on oNB remain the dominant technology to study signal transduction mediated by biomolecules despite limitations like slow analyte-release kinetics, the requirement of UV light for photolysis and the formation of potentially toxic nitroso photoproducts. [18] In addition to these shortcomings, incorporating ligands into an oNBscaffold can interfere with the uncaging mechanism. Both classes of photocaged complexes described above often exhibit low quantum yields (< 5 %) owing to resonance between receptor donor atoms and the reactive aci-nitro intermediate generated by irradiating oNB chromophores.…”
mentioning
confidence: 99%
“…[15] In particular by using red or IR light and applying two-photon irradiation technologies or using upconversion techniques, penetration depths of up to 10 mm can be achieved. [13,14,23,24] .…”
Section: Methodsmentioning
confidence: 99%
“…[13,14] Several studies concerning the light-induced activation of nucleic acids with "caged" oligonucleotides have been published. [15] Two studies investigated the use of light-induced regulation of miRNA expression and showed that lightactivated antagomirs directed against miR-122 and miR-21, in the first study, and an antisense oligonucleotide against a C. elegans miRNA, in the second study, can be used to block miRNA expression in model systems. [16,17] The two studies made use of artificial reporter proteins or manipulated organisms.…”
mentioning
confidence: 99%
“…[13,14] In den letzten Jahren wurden etliche Studien zur lichtinduzierten Aktivierung von Nukleinsäuren mit photoaktivierbaren ("caged") Oligonukleotiden verçffentlicht. [15] In zwei dieser Studien wurde die lichtinduzierte Regulation der miRNA-Expression untersucht. Durch Verwendung lichtaktivierbarer Antagomirs gegen miR-122 und miR-21 in der einen Studie sowie eines lichtaktivierbaren Antisense-Oligonukleotids gegen eine miRNA aus C. elegans in der anderen Studie gelang es, die miRNA-Expression in Modellsystemen zu inhibieren.…”
unclassified
“…[9,21,22] Zudem wurde in einer kürzlich publizierten Studie über die sichere und effiziente Verwendung von AntimiRs gegen miR-122 im Menschen berichtet. [12] [15] Durch Verwendung von rotem oder IR-Licht und mithilfe der Zweiphotonenbestrahlung oder aufkonvertierender Nanopartikel kçnnten sich Eindringtiefen in biologisches Gewebe von bis zu 10 mm erzielen lassen. [13,14,23,24] Eingegangen am 26.…”
unclassified